Forsyth County Public Library construction, 1952. - Unknown (Forsyth County Public Library, 1952)
TCS 7/12/52.
Forsyth County Public Library construction.
Keywords: Forsyth County Public Library; Digital Forsyth; Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works; Winston-Salem (N.C.)